Experimental two-step universal adhesives bond durably in a challenging high C-factor cavity model. Issue 1 (January 2023) - Tang, Chuliang; Ahmed, Mohammed H.; Yao, Chenmin; Mercelis, Ben; Yoshihara, Kumiko; Peumans, Marleen; Van Meerbeek, Bart
Abstract: Objectives: To determine the bonding effectiveness of experimental 2-step universal adhesives (UAs) to high C-factor class-I cavity-bottom dentin and to assess the potential bond-strength contribution of an additional flowable composite layer. Methods: Three experimental 2-step UA formulations, involving the application of a 10-MDP-based primer followed by a hydrophobic adhesive resin with a 15-to-20-µm film thickness and differing only for filler, referred to as BZF-21 (silica and bioglass filler), BZF-29 (silica filler) and BZF-29_hv (higher silica-filler loading resulting in a higher viscosity), all prepared by GC, along with three representative commercial adhesives, Clearfil SE Bond 2 (C-SE2, Kuraray Noritake), G-Premio Bond (G-PrB, GC) and OptiBond FL (Opti-FL, Kerr), were comparatively investigated for their 'immediate' and 'aged' (50, 000 thermocycles) micro-tensile bond strength (μTBS), when applied either in etch-and-rinse (E&R) or self-etch (SE) mode, to high C-factor class-I cavity-bottom dentin (n = 10; 10 experimental groups). Four additional experimental groups involved the extra application of the flowable composite G-ænial Universal Flo (GC), employed as an intermediate liner in combination with the adhesives BZF-29 and G-PrB and again applied both in E&R or SE mode. Statistical analysis was performed using linear mixed-effects (LME) modelling and linear regression analysis (p < 0.05). Results: All 2-step UAs performed similarly when compared to the gold-standard E&R Opti-FL and SE C-SE2 adhesives, except for the aged μTBS of BZF-29_hv applied in E&R mode, and significantly outperformed the 1-step UA G-PrB. Significant reduction in μTBS upon aging was only recorded for 2-step UAs applied in E&R mode. The extra flowable composite layer significantly improved G-PrB's μTBS. Significance: The experimental 2-step UAs revealed favorable bonding performance in the challenging high C-factor class-I cavity model, comparable to that of the multi-step gold-standard E&R and SE adhesives and superior to that of the 1-step UA investigated. An additionally applied flowable composite layer compensated for the lower bonding effectiveness of the 1-step UA in the high C-factor cavity model. Highlights: Hydrophobic HEMA-free 2-step universal adhesives achieve reliable bonding effectiveness in high C-factor conditions. Multi-step adhesives applied in a thick film better absorb polymerization-contraction stress generated in class-I cavities. Extra applied flowable composite compensates for the lower bond strength of 1-step universal adhesives in class-1 cavities.